2016
DOI: 10.1371/journal.pone.0159717
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Kidney Graft Survival in Low Immunological Risk Patients Showing Inflammation in Normal Protocol Biopsies

Abstract: IntroductionThe pros and cons for implementing protocol biopsies (PB) after kidney transplantation are still a matter of debate. We aimed to address the frequency of pathological findings in PB, to analyze their impact on long-term graft survival (GS) and to analyze the risk factors predicting an abnormal histology.MethodsWe analyzed 946 kidney PB obtained at a median time of 6.5 (±2.9) months after transplantation. Statistics included comparison between groups, Kaplan-Meier and multinomial logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…Secondly, biomarkers may be superior to serum creatinine measurement in detecting the presence or absence of subclinical rejection, which normally would stay below the radar of detection when using merely serum creatinine as indicator. Subclinical rejection has an incidence of 5% within the first 6 months after transplantation (47) and significantly impacts long-term graft survival (48).…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Secondly, biomarkers may be superior to serum creatinine measurement in detecting the presence or absence of subclinical rejection, which normally would stay below the radar of detection when using merely serum creatinine as indicator. Subclinical rejection has an incidence of 5% within the first 6 months after transplantation (47) and significantly impacts long-term graft survival (48).…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…The incidence of both clinical and subclinical acute rejection was low, in line with the results achieved with current immunosuppression in the low immunological risk population. 33 There were no differences between PAR and CAL regarding rejection and de novo donor-specific antibody development. These findings suggested that PAR, in comparison with nutritional vitamin D replenishment, was not associated with a higher prevention of immunologically mediated allograft damage.…”
Section: Discussionmentioning
confidence: 91%
“…We arbitrarily employed an i-score ≥ 1 as the threshold to distinguish between inflammation and no inflammation. This decision was based on previous observations showing that an i-score ≥ 1 is associated with decreased graft survival, while isolated tubulitis has a minor and controversial influence on outcome [ 35 , 36 , 37 ]. Despite the low degree of inflammation, TAC levels were significantly higher in early biopsies without inflammation, and the time below the therapeutic range was longer in late biopsies, suggesting that even in low immunological risk patients receiving a high TAC schedule, interstitial inflammation in healthy interstitial areas is modulated by TAC exposure.…”
Section: Discussionmentioning
confidence: 99%